The new beginning : a business novel on how to successfully implement the combination of the Theory of Constraints, Lean, and Six Sigma to drive profit margins - Sproull, Robert; Hutcheson, Matt (Productivity Press, 2021)
This book is a sequel to the business novel, The Secret to Maximizing Profitability - A Business Novel on How to Successfully Combine the Theory of Constraints, Lean, and Six Sigma to Drive Profit Margins to New Levels. In The New Beginning, Tom Mahanan, Tires for All's former Director of Finance, who learned how to combine the Theory of Constraints with Lean and Six Sigma, and then applied it to Tires for All, to take his company to levels of profitability they had never experienced before. As a reward for his work, Tom was given a permanent seat on the Board of Directors, as long as he continued his improvement work at the remaining portfolio of companies owned by the Board of Directors. Tom performed extremely well, but one day he receives a life-changing phone call from his former mentor, Bob Nelson, the man who he had worked with at Tires for All to make amazing improvements. Bob asks him to play golf with him and two others, Jeff Johnson, from Toner International, and Pete Hallwell, the CFO at Maximo Health Center Complex. Pete and Tom share a golf cart during the round and begin chatting about the work Tom had done at Tires for All and the other portfolio of companies. Pete, who works for a healthcare complex of hospitals, is so impressed with the results Tom had achieved, that he invites him to lunch the following week. Tom accepts his offer of lunch and ultimately, Tom signs a consulting agreement with Pete. Tom had provided an example from a previous improvement effort where he worked with a hospital in Chicago to improve their Emergency Department time for STEMI-type heart attack patients. In his explanation, Tom presents a variety of improvement tools which includes the integration of the Theory of Constraints, Lean, and Six Sigma. Tom then meets with his current employer and specifically, the Chairman of the Board of Directors, Jonathan Briggs, to let him know that he will be resigning to form his own consulting firm. Jonathan then surprises Tom by offering him a consulting agreement to improve all of their portfolio companies. The remainder of the book is all about teaching companies how to combine the Theory of Constraints, Lean, and Six Sigma to obtain optimal results. In the final two chapters, a new problem surfaces, which is the Corona Virus. Essentially, this book teaches the reader how to successfully combine and implement the Theory of Constraints, Lean, and Six Sigma to produce results that many companies only dream of having. It covers a variety of different company types including manufacturing and healthcare.